Consumer sensory analysis of high flavonoid transgenic tomatoes - Lim, Wansang; Miller, Rebecca; Park, Jung-Eun K.; Park, Sunghun (My University, 2014)
Tomatoes have ameliorative effects on cardiovascular disease and cancer (Agarwal and Rao 2000; Rao 2002). In this study, metabolic engineering of flavonoids was utilized to improve the nutritional value of tomatoes by increasing flavonol and anthocyanin content. Total flavonol content was significantly increased in both the peel and flesh using the onion chalcone isomerase (CHI) gene. The Delila (Del) and Rosea1 (Ros1) genes from the snapdragon Antirrhinum majus were concomitantly expressed to produce an anthocyanin‐rich tomato which was purple in color. Sensory evaluation by a panel of 81 untrained consumers revealed no significant difference in liking of color or texture between CHI, Del/Ros1, and wild‐type tomatoes. Consumers reported marginal but significantly higher preference for the flavor and overall liking of CHI tomatoes over Del/Ros1 and wild‐type tomatoes. This study is the first to report the results of sensory tests of transgenic tomatoes by a consumer panel representing the general consuming public.
Keywords: Flavonoids; Transgenic; Liking; Tomato; Sensory